Pull-Out Forming: Experiments and Process Simulation - Kumar S.; Chaudhary R. (My University, 2025)
Pull-out forming is a forming process/technology wherein a tubular work material is pulled out from a hole opening at the surface of a tube to produce a product that is used to join with another tube for a high-pressure application. This forming process results in good accuracy, surface finish, better mechanical and metallurgical properties at a lower unit cost. A simulation methodology has been proposed for the pull-out forming process including design validation and experiments. The experimental set-up is fabricated to carry out several test runs to validate the simulation. The FE simulation study of pull-out process has been done at room temperature on tubular shape workpiece of pure aluminium metal. The result is used to investigate the effective stress distribution, maximum deforming load and the wall thickness of pull-out under various process parameter conditions (speed, friction, no. of pull-out, etc.). Furthermore, the pull-out forming process has been optimized in order to get the uniform thickness and defect free product. © 2019, Springer Nature Singapore Pte Ltd.